Participatory cocoa (Theobroma cacao) selection in Cameroon: Phytophthora pod rot resistant accessions identified in farmers fields - Efombagn, M.I.B.; Nyassé, S.; Sounigo, O.; Kolesnikova-Allen, M.; Eskes, A.B. (Elsevier, 2007)
As part of a participatory selection programme, promising individual trees were selected in 2004 in cocoa farms of southern and western Cameroon regions for yield and for low incidence of Phytophthora pod rot (Ppr) caused by Phytophthora megakarya. The aim of this study was to compare the levels of resistance to Ppr between farm accessions (FA), introduced and local genebank accessions (GA). In total, 234 FA were grafted in the nursery together with 22 introduced GA and 73 local GA, and tested for resistance to P. megakarya by leaf disc inoculations. The introduced GA, that were reported as resistant to Ppr in other countries, proved to be more resistant than the selected FA and unselected FA and also more resistant than the 3 control clones for Ppr resistance used in the study. However, approximately 10% of the FA were as resistant as the average of the introduced GA, showing the potential of selection for resistance to Ppr in farmers’ fields. The average level of resistance of the FA was relatively higher than that of the local GA. The FA selected for yield and low Ppr incidence in the field were more resistant in the leaf disc test than the unselected FA. The use of FA and of farmers’ knowledge in the participatory selection process is valuable in obtaining Ppr-resistant cultivars.